A comparative study and characterization of Azadirachta indica mediated nano‐insecticide and ethanolic extract against mosquito vectors – Arabian and Indian strains. Issue 11 (26th October 2021) - Aziz, Al Thabiani
Abstract: Vector borne disease are found all over the world, this becomes a major economic and social problem in developing and developed countries. Chemical insecticides have quieted their action by developed resistance, environment contaminations, non‐target effects on beneficial insects etc . Ethanolic extracted Azadirachta indica has shown virtuous mortality against Indian strains Aedes aegypti, Anopheles stephensi, Culex quinquefasciatus and Arabian strains Cx. pipiens, Ae. aegypti . The green synthesized AgNPs insecticide developed from Az. indica which was characterized through UV, TEM, EDX, XRD showed notable larvicidal and adulticidal activity at lower concentrations when compared with ethanolic extract. The lethal concentration LC50 and LC90 of larvae by nano‐insecticide was 30.8, 63.01 μg/mL, ( An. stephensi), 33.5, 71.5 μg/mL (Ae. aegypti), 39, 81.4 μg/mL ( Cx. quinquefasciatus ) against Indian strains and 62.5, 100.8 μg/mL ( Ae. aegypti ), 61.2, 92.04 μg/mL ( Cx. pipiens ). The adulticidal activity of AgNPs for LC50 and LC90 against Arabian strain was 20.1, 92.0 μg/mL against Ae. aegypti, 367.8, 1521.7 μg/mL against Cx. pipiens . The larvicidal and aduticidal activity of AgNPs developed from Az. indica was superior to crude ethanolic leaf extract. Thus AgNPs are a promising potential larvicidal, adulticidal insecticide against Cx. quinquefasciatus, Cx. pipiens, Ae. aegypti and An. stephensi .